The Influence of eWOM and Brand Image on Brand Trust and Purchase Intention of Mixue Ice Cream & Tea Consumers in the Special Region of Yogyakarta - Marziqah, Raihanah; Albari, Albari (Profesional Muda Cendekia Publishing, 2023)
This research aims to explain the influence of electronic word of mouth (eWOM), brand image, brand trust, and consumer purchase intention on Mixue ice cream and tea. The respondents of this study were 190 individuals from the Yogyakarta Special Region, aged between 15 and 50 years old. Convenience sampling technique was used for sample selection, and the structural equation modeling (SEM) analysis technique was employed to test the model and hypotheses. The testing was conducted using Smart PLS Version 3.2.9 software. The results of this study indicate that eWOM has a positive and significant influence on purchase intention. eWOM also has a positive and significant influence on brand image, and a positive and significant influence on brand trust. Brand image has a positive and significant influence on brand trust, and a positive and significant influence on purchase intention. Lastly, brand trust has a positive and significant influence on purchase intention.